1997
DOI: 10.1002/(sici)1097-0231(19971015)11:15<1649::aid-rcm67>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

A new technique for decomposition of selected ions in molecule ion reactor coupled with ortho-time-of-flight mass spectrometry

Abstract: A molecule ion reactor (MIR), i.e. a gas filled radio-frequency only quadrupole with a longitudinal electrical field (RFQLEF), is used as an atmospheric pressure ionization interface for an orthogonal time-of-flight mass spectrometer (O-TOFMS). A new phenomenon of selective ion 'heating' in a MIR near Mathieu's instability threshold was found and confirmed by computer simulation. The 'heating' in collisions with buffer gas molecules leads to ion decomposition. In the case of multicharged ions, fragments with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
67
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 6 publications
(10 reference statements)
0
67
0
Order By: Relevance
“…The cooling of the ions to the center of the trap also helps to improve mass resolution and mass accuracy by minimizing the effects due to difference in initial conditions for the mass selective instability scan [8,25,26]. The fragmentation of the ions for tandem mass spectrometry also relies on their collisions with the buffer gas molecules, which can cause increased ion internal energies and lead to subsequent fragmentation [27][28][29][30][31]. For each of these steps, dedicated experimental conditions are used to reach a balance between providing adequate collision energies and minimally interfering with intentionally stable ion trajectories.…”
mentioning
confidence: 82%
“…The cooling of the ions to the center of the trap also helps to improve mass resolution and mass accuracy by minimizing the effects due to difference in initial conditions for the mass selective instability scan [8,25,26]. The fragmentation of the ions for tandem mass spectrometry also relies on their collisions with the buffer gas molecules, which can cause increased ion internal energies and lead to subsequent fragmentation [27][28][29][30][31]. For each of these steps, dedicated experimental conditions are used to reach a balance between providing adequate collision energies and minimally interfering with intentionally stable ion trajectories.…”
mentioning
confidence: 82%
“…For example, generation of an axial electric field by segmenting the multipole rods themselves has been extensively characterized [11][12][13][14][15][16][17]. Other methods for producing an axial electric field include conical (rather than fixed-diameter) multipole rods [18], offsetting one end of the multipole from the central (z-) axis [14], encasing the multipole with segmented rings [15,19], and the insertion of electrodes between parallel rods [20,21].…”
Section: T He Interface Of Electrospray Ionization (Esi) Withmentioning
confidence: 99%
“…Of particular importance is the collisional activation of ions in radio frequency (RF) ion traps and guides, where a substantial bath gas pressure and long residence times result in large numbers of the ionneutral collisions [6]. Several research groups have proposed using the effective temperature as a measure of ion activation under conditions of multiple ionneutral collisions [7][8][9][10][11][12]. As such, the effective temperature concept proved to be very useful in the interpretation of ion activation data obtained for various mass spectrometry experiments, in particular in quadrupole ion trap experiments [8,9,[13][14][15].…”
mentioning
confidence: 99%
“…We consider the kinetics of collisional heating of ions using the characteristic ion heating time. It was previously suggested that this characteristic time is of the same order of magnitude as the velocity relaxation time [10]. Here, we present a more accurate estimation of the characteristic ion heating time based on recent findings for the thermal energy in polyatomic biomolecules, including peptide ions [23].…”
mentioning
confidence: 99%